التردد على مواقع التواصل الاجتماعي وعلاقتها ببعض المشكلات الاجتماعية لدى عينة من طلبة كلية التربية بجامعة دمشق - نعيسة, رغداء علي (Latakia University Journal - Arts and Humanities Sciences Series, 2016)
يهدف البحث إلى: - تعرف درجة التردد على مواقع التواصل الاجتماعي لدى طلبة كلية التربية في جامعة دمشق. - تعرف المشكلات الاجتماعية الشائعة لدى طلبة كلية التربية في جامعة دمشق. - تعرف العلاقة بين التردد على مواقع التواصل الاجتماعي وبين المشكلات الاجتماعية. - تعرف دلالة الفروق في إجابات أفراد عينة البحث على استبانة التردد على مواقع التواصل الاجتماعي ومقياس المشكلات الاجتماعية وفق متغيرات البحث: (عدد سنوات التردد على مواقع التواصل الاجتماعي، عدد ساعات الاستخدام). واعتمدت الباحثة على المنهج التحليلي، واستخدمت أداتي البحث:(استبانة التردد على مواقع التواصل الاجتماعي، ومقياس المشكلات الاجتماعية). وشملت عينة البحث (400) طالباً وطالبةً في كلية التربية في جامعة دمشق. ومن أهم النتائج التي توصل إليها البحث: 1) وجود علاقة ارتباطيه إيجابية ذات دلالة إحصائية بين التردد على مواقع التواصل الاجتماعي وبين المشكلات الاجتماعية لدى طلبة جامعة دمشق. 2) وجود فروق ذات دلالة إحصائية بين متوسط إجابات أفراد عينة البحث على استبانة التردد على مواقع التواصل الاجتماعي وفق متغير سنوات استخدام شبكات التواصل لصالح الطلبة الذين كانوا يستخدمون شبكات التواصل منذ مدة 5 سنوات فأكثر. 3) 4) وجود فروق ذات دلالة إحصائية بين متوسط إجابات أفراد عينة البحث على مقياس المشكلات الاجتماعية وفق متغير سنوات التردد على مواقع التواصل لصالح الطلبة الذين كانوا يستخدمون شبكات التواصل منذ مدة 5 سنوات فأكثر. الكلمات المفتاحية: مواقع التواصل الاجتماعي، المشكلات الاجتماعية، طلبة الجامعة. The research aims to: - Learn about the degree of Hesitation on the social networking sites with students of the Faculty of Education at the University of Damascus. - Learn about common social problems among students of the Faculty of Education at the University of Damascus. - Learn about the relationship between the Hesitation of social networking sites and social problems. - Know the significance differences in the answers to the research sample to identify Hesitation of social networking sites and measure social problems according to the members of the search variables: (number of years of Hesitation on the social networking sites, the number of hours of use). And adopted a researcher on the analytical method, and used two tools Search: (Hesitation questionnaire on social networking sites, and the measure of social problems). The research sample included 400 students in the College of Education at the University of Damascus. Among the most important findings of the research: 1) there is a positive correlation statistically significant differences between Hesitation of social networking sites and social problems at Damascus University students. 2) there are significant differences between the average sample answers to a questionnaire on the Hesitation of social networking sites members according to the use of variable years networking for the benefit of students who were using networks since a period of 5 years or more. 3) the presence of statistically significant differences between the average answers the research sample differences on a scale of social problems, according to a variable-year frequency networking sites for the benefit of students who were using communication networks, since a period of 5 years or more.